Autecology of Castanopsis argentea (Blume) A.DC. in Telaga Warna Nature Reserve Area, Bogor Regency - Dianti Mayadika Putri; Sulistijorini Sulistijorini; Nina Ratna Djuita (Universitas Gadjah Mada, 2022)
The red list of the International Union for the Conservation of Nature and Natural Resources (IUCN) reported Castanopsis argentea as an endangered species. Studies about autecology on its natural habitat become important to perform species conservation. This study aimed to analyze the population structure, distribution pattern, and environmental factors that influence the presence of C. argentea in the Telaga Warna Nature Reserve. Data was collected in September 2020 by making 21 plots with a single plot. The purposive sampling method was used based on C. argentea representatives to determine plot location. Measurement of environmental factors, including soil sampling was carried out on each plot. Population structure was analyzed based on plant density, and Morisita index determined the distribution pattern. Environmental data were analyzed using PCA with Minitab 19 programs. Our field observation showed that C. argentea seedling has the highest density (1071 ind/ha) and decreased in the mature phase. C. argentea was found to have a clumped distribution pattern with an Id value of 1.03. PCA analysis showed differences in environmental factors that were thought to influence the presence of C. argentea individuals in four growth phases. The highest population structure of C. argentea was found in the growth phase of seedlings and saplings at an altitude of 1400 m asl. The spread population distribution of C. argentea was clumped. The influences of environmental variables on the existence of C. argentea were Mg, Ca, CEC, pH, and soil moisture.